Lions and Librarians: a Plea for the Intelligent Conservation of an Unnecessarily Endangered Species. (June 2019) - Greenberg, Daniel
Abstract: The role of the law librarian or legal information professional is thought by some to have been diminished significantly by technological advances which provide instant access to an enormous range of materials direct to individual users at their desks. The reality is that the wide range of instantly accessible materials makes the experience and knowledge of the information professional more important, not less; and imminently expected advances in machine learning and artificial intelligence are likely to confirm the vital importance of the legal information professional at the centre of legal services.